Surgical Treatment Tactics of Injuries of the Anterior Cruciate Ligament in the Acute Period (Literature Review) - Kostrub, O.O.; Blonskyi, R.I.; Volos , O.V. (TERRA ORTHOPAEDICA, 2024)
Summary. The article presents a theoretical and practical rationale for modern aspects of the clinical picture, diagnosis and treatment of anterior cruciate ligament injury in the acute period, according to domestic and foreign literature.